p53–GSDME Elevation: A Path for CDK7 Inhibition to Suppress Breast Cancer Cell Survival - Wang, Yueyuan; Peng, Jingyu; Mi, Xuguang; Yang, Ming (Frontiers in Molecular Biosciences, 2021)
Purpose: Cyclin-dependent kinase (CDK7), as a pivotal part of both CDK-activating kinase (CAK) and transcription factor IIH (TIIH), mediates cell cycle and transcription activity. Higher CDK7 expression is a character of breast cancer and indicates poor prognosis. Inhibiting CDK7 exhibited effective cancer cells suppression which implies the potential of CDK7 inhibition to be a method for anti-cancer treatment. Although several possibilities to repress cancer cells survival under CDK7 inhibition have been proposed, our study aimed to explore a novel mechanism for suppressing breast cancer survival of CDK7 inhibition. Methods: We utilized two different inhibitors targeting CDK7, which are THZ1 and LDC2497, to treat breast cancer cell lines. We here carried out CCK8 assay, colony formation assay, apoptosis assay to detect the anti-tumor effect of THZ1 and LDC4297. The protein levels of CDK7, p53 and GSDME were determined by western blotting assay. Transfection assay and lentiviruses creation were meant to knockdown the expressions of GSDME, CDK7 and p53. Results: Transcriptome displayed that CDK7 was higher in breast cancer comparing with normal breast tissue. Inhibiting CDK7 in breast cancer cells repressed breast cancer proliferation and colony formation, increased apoptotic cell rate, elevated protein levels of p53 and GSDME. According to bioinformatics databases and experiments of cell biology, GSDME expression in breast cancer was lower. Repressing GSDME expression in breast cancer cells contributed proliferation and colony formation successfully. Inhibiting p53 in MCF-7 cells, stronger proliferation and colony formation was shown, and decreased GSDME expression. Furthermore, p53 inhibition blocked the elevation of GSDME mediated by CDK7 inhibition and retrieved cells from CDK7 inhibition negative effect. These results revealed CDK7-p53-GSDME axis could be a pathway to affect breast cancer cells survival. Conclusion: CDK7 inhibition exerted a negative effect to breast cancer cells proliferation, colony formation in p53-GSDME dependent manner.